Rice Shoot 13C Abundance at Maximum Tillering Stage Is Well Suited to Distinguish Differences in Water Use Efficiency for Water-Saving Rice Technologies - Tao, Yueyue; Zhang, Yanan; Dittert, Klaus; Guo, Lin; Liu, Meiju; Lin, Shan (Agronomy (Basel), 2024)
Water availability is one of the most limiting factors in crop production, and understanding crop water use efficiency is especially important in environments where changes in crop performance are driven by water availability. The stable isotope δ13C has been proposed to evaluate the water management and physiological water use efficiency (WUE) for upland crops. However, this technique has rarely been used for rice, especially for water-saving management systems such as the Ground Cover Rice Production System (GCRPS), which can significantly improve WUE. Therefore, a two-year lowland rice field experiment was conducted to evaluate the effects of sampling time, plant organ and yearly climatic changes on δ13C and its relationship to WUE. Our study revealed the following: (1) Significant differences in shoot and leaf δ13C were found between paddy and GCRPS plants only at the maximum tillering stage but not at the flowering stage. (2) The shoot δ13C at maximum tillering showed a significant positive correlation with irrigation (WUEi) and total water use efficiency (WUEt), but there was no such relationship at the flowering stage. (3) Shoot δ13C was significantly higher in 2013 than in 2014, most likely related to higher solar radiation from transplanting to maximum tillering in 2013, as there were no significant differences between the years in other climatic factors and soil water content. Our results suggest that the δ13C of rice shoots sampled at the maximum tillering stage shows the best correlation with crop water use efficiency.